2013
DOI: 10.1159/000353679
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke with Thiazolidinediones: A Ten-Year Nationwide Population-Based Cohort Study

Abstract: Background: Thiazolidinediones (TZDs) - rosiglitazone and pioglitazone - a class of insulin sensitizer for treating type 2 diabetes, have been reported to exhibit neuroprotective effects in preclinical studies and have good effects in the control of blood sugar for diabetic patients with insulin resistance. However, clinical trials and observational studies have raised the possibility of higher stroke risk in patients treated with rosiglitazone. Whether pioglitazone poses similar stroke risk remains uncertain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…A cohort study involving diabetic patients without prior stroke showed that individuals who had used rosiglitazones, a type of thiazolidinedione (TZD), for 10 years presented an increased risk of ischemic stroke and heart failure (30). Furthermore, the long-term use of rosiglitazones has been associated with bone loss and fracture risk (31).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study involving diabetic patients without prior stroke showed that individuals who had used rosiglitazones, a type of thiazolidinedione (TZD), for 10 years presented an increased risk of ischemic stroke and heart failure (30). Furthermore, the long-term use of rosiglitazones has been associated with bone loss and fracture risk (31).…”
Section: Discussionmentioning
confidence: 99%
“…Δ2-troglitazone was seen to be more potent at reducing cell proliferation in cancer cells 179 and may have a different side-effect profile to troglitazone 180 . However, similarly to efatutazone, phase 2 trials for troglitazone have been disappointing 181,182 uncovering little clinical value in this PPARγ ligand. There have also been some concerns regarding the risk of harmful cardiovascular effects of thiazolidinediones, especially for rosiglitazone 183 .…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…It should be highlighted that baseline adiponectin levels do not predict the response to glitazones [105]. Anyway, the use of glitazones to increase adiponectin is discouraged due to the potential adverse cardiovascular effects of these drugs, like heart failure or stroke [106], especially in the case of rosiglitazone [107]. The sulfonylurea glimepiride yields also positive effects on adiponectin, particularly in elderly T2DM patients [108].…”
Section: Introductionmentioning
confidence: 99%